Peningkatan Aktivitas Dan Hasil Belajar IPA Menggunakan Model Quantum Learning Pada Siswa Kelas 4A SDI Bhoanawa 1 - Martha Lede (Program Studi Pendidikan Ekonomi, Universitas Flores, 2020)
This study aims to improve the activities and learning outcomes of grade 4A students at SDI Bhoanawa 1 through the application of the Quantum Learning model. This research is a classroom action research with the stages plan, action, observe and reflect. The research subjects were 23 students of grade 4A SDI Bhoanawa 1. Data obtained by observation, tests and interviews. Data were analyzed with simple statistics to determine the percentage of individual and classical completeness of each cycle. The results showed that after the quantum learning model was applied for two cycles, there was an increase in activity and science learning outcomes in grade 4A SDI Bhoanawa 1 students.